Sosiologi Bourdieu Melihat Poster Film Horor Indonesia - Fitro Nur Hakim (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to analyze the design of Indonesian horror film posters through Pierre Bourdieu's sociological lens. The main focus of the study is to understand how the visual elements in the poster reflect the social dynamics, culture, and structure of the film industry. By using the concepts of habitus, capital (cultural, symbolic, economic), field, doxa, and social reproduction, this study reveals that the design of horror film posters not only functions as a promotional tool, but also as a medium that reproduces local cultural values ​​and community beliefs about the supernatural world. Elements such as traditional ghosts such as genderuwo, kuntilanak and mystical symbols such as keris, offerings, then there are dark colors, and a scary atmosphere reflect the habits of audiences who are familiar with local myths. This study also shows that horror film posters reproduce stereotypes about the relationship between humans and the supernatural world, and strengthen the hierarchy of spiritual power through visual symbols. These findings confirm the relevance of Bourdieu's theory in understanding cultural phenomena through visual media. This study is expected to provide new insights for filmmakers, graphic designers, and students in understanding the interaction between culture, aesthetics, and the film industry.